Climate Services for Resilient Development: Success Stories - Krupnik, Timothy J. (2019)
Climate Services for Resilient Development (CSRD) is a global partnership whose core mission is to translate actionable climate information into easy to understand formats to spread awareness and use of climate services. The CSRD consortium in South Asia is led by the International Maize and Wheat Improvement Center (CIMMYT) in partnership with the Bangladesh Meteorological Department (BMD), Bangladesh Department of Agricultural Extension (DAE), Bangladesh Agricultural Research Council (BARC), Bangladesh Agricultural Research Institute (BARI), International Center for Integrated Mountain Development (ICIMOD), International Institute for Climate and Society (IRI), University de Passo Fundo (UPF), and the University of Rhode Island (URI).